Multidimensional strategies for sustainable management of cocoa by-products - Santos, Lívia de Matos; Ferreira Ribeiro, Camila Duarte; Alves, Janaína de Carvalho; da Silva, Isadora Santana Araújo; Silva, Vanessa de Lima; Santos, Isabelle Palma Patrício; Roselino, Mariana Nougalli (Frontiers in Sustainable Food Systems, 2024)
The limited understanding of the potential applications of cocoa by-products, due to the scarcity of studies that integrate scientific research and patent analysis, hinders the proper use of these by-products and compromises their role in promoting sustainability in the food industry. The utilization of cocoa by-products is of great interest due to their potential to drive sustainable growth in the food industry. However, a comprehensive understanding of their use and potentialities requires an analysis that incorporates both scientific research and patent analysis. Methodology: In this study, a multidimensional review encompassing scientific and patentometric analyses of cocoa by-products was conducted. The Ddatabases (Web of Science, Scopus, and Medline/PubMmed) were utilized with search terms (Cocoa* OR Theobroma cacao AND by-product*) to identify scientific articles (144). Additionally, we explored patent2earch2 databases (Espacenet and National Institute of Industrial Property (INPI)), employing a combination of search2earch terms and international classification codes (Cocoa* OR Theobroma cacao AND by-product* AND A23G), were also applied to identify the generated technologies (73).The results revealed a significant concentration of scientific research in the agricultural and biological sciences areas (68%), focusing with a particular focus on the bioactive and biofunctional compositions of the cocoa by-products. Additionally, an interest in technological innovation related to these by-products was identified, as evidenced by the increased in the number of patent registrations after the year 2020. These findings suggest a significant potential for growth in this sector growth and provide valuable insights for future research and product development within in the food industry.